'Nothing can be done until everything is done': the use of complexity arguments by food, beverage, alcohol and gambling industries. Issue 11 (4th October 2017) - Petticrew, Mark; Katikireddi, Srinivasa Vittal; Knai, Cécile; Cassidy, Rebecca; Maani Hessari, Nason; Thomas, James; Weishaar, Heide
Abstract : Background: Corporations use a range of strategies to dispute their role in causing public health harms and to limit the scope of effective public health interventions. This is well documented in relation to the activities of the tobacco industry, but research on other industries is less well developed. We therefore analysed public statements and documents from four unhealthy commodity industries to investigate whether and how they used arguments about complexity in this way. Methods: We analysed alcohol, food, soda and gambling industry documents and websites and minutes of reports of relevant health select committees, using standard document analysis methods. Results: Two main framings were identified: (i) these industries argue that aetiology is complex, so individual products cannot be blamed; and (ii) they argue that population health measures are 'too simple' to address complex public health problems. However, in this second framing, there are inherent contradictions in how industry used 'complexity', as their alternative solutions are generally not, in themselves, complex. Conclusion: The concept of complexity, as commonly used in public health, is also widely employed by unhealthy commodity industries to influence how the public and policymakers understand health issues. It is frequently used in response to policy announcements and in response to new scientific evidence (particularly evidence on obesity and alcohol harms). The arguments and language may reflect the existence of a cross-industry 'playbook', whose use results in the undermining of effective public health policies – in particular the undermining of effective regulation of profitable industry activities that are harmful to the public's health.